ANALISIS PROFITABILITAS PADA INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA - Wehelmina M Ndoen (Journal of Management Small and Medium Enterprises (SMEs), 2019)
This research aims to investigate the Return On Investment (ROI), Return On Equity (ROE),Net Profit Margin (NPM) and Earning Per Share (EPS) of Consumer Goods Industry inIndonesia Stock Exchange year 2013-2015. The samples are 12 companies determined bypurposive sampling technique. Results obtained that the ROI, ROE, NPM and EPS can notbe the tool of decision for investors because of the fluctuation results in year 2013-2015 Keywords : Profitability, Return On Investment (ROI), Return On Equity (ROE), Net ProfitMargin (NPM), Earning Per Share (EPS)